(untitled) (Journal of actual problems of jurisprudence, 2019)
This article examines the legal problems of food and veterinary safety in the Republic of Kazakhstan. The author suggests some ways to improve the state mechanism in the area of food safety and veterinary. Key words: veterinary safety, food safety, food, genetically modified foods, the sign of net output.